Effects of antifouling compounds on the growth of macroalgae Undaria pinnatifida. (January 2023) - Nomura, M.; Okamura, H.; Horie, Y.; Yap, C.K.; Emmanouil, C.; Uwai, S.; Kawai, H.
Abstract: Seaweeds are some of the principal primary producers of marine environments, and they are important ecological elements of coastal ecosystems. The effects of harmful chemicals on seaweeds may adversely affect coastal ecosystems, hence we aimed to develop a new phytotoxicity test using the gametophytes of a common temperate kelp species, Undaria pinnatifida (KU-1630), for the widely used antifouling chemical substances Cybutryne, Diuron, Cu 2+, and Zn 2+ . Toxicity to gametophytes of U. pinnatifida was assessed by comparing the relative growth rate (RGR) at the logarithmic growth phase. Fragmentation method, initial algal biomass, photon irradiance, and adhesive period were investigated for developing optimal test conditions. Cybutryne exposure tests were performed with seven replicates and control, the RGR ranging from 0.17 to 0.19, while mean 7-day EC50 and no observed effect concentration (NOEC) were 5.1 μg/L and 1.8 μg/L, respectively. The 7-day EC50 for other antifoulants was 14 μg/L for Diuron, 17 μg/L for Cu 2+, and 1500 μg/L for Zn 2+ . This test method demonstrated high sensitivity and reproducibility, and it may be added to the routine methods used for toxicity evaluation of hazardous chemicals. Graphical abstract: Image 1 Highlights: Toxicity test method was developed using the gametophytes of Undaria pinnatifida. Algal biomass was measured using in vivo chlorophyll fluorescence. Toxicity test showed high reproducibility to Cybutryne. RGR based EC50 for antifouling compounds showed good sensitivity.